2017
DOI: 10.1080/10641963.2016.1235184
|View full text |Cite
|
Sign up to set email alerts
|

Renin–angiotensin system blockade alone or combined with ETA receptor blockade: effects on the course of chronic kidney disease in 5/6 nephrectomized Ren-2 transgenic hypertensive rats

Abstract: When applied in the advanced phase of CKD, addition of ET receptor blockade to the complex RAS blockade brings no further beneficial renoprotective effects on the CKD progression in 5/6 NX TGR, in addition to those seen with RAS blockade alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 41 publications
3
38
1
Order By: Relevance
“…For many years it has been well reported that RAS inhibition protects against renal interstitial fibrosis induced by UUO 69 , 71 73 . RAS activation has also been implicated in the development of cardiac fibrosis in CKD and ESRD patients 74 78 . Evidence from multiple randomized clinical trials supports the notion that inhibiting the RAS improves all causes of mortality and reduces adverse cardiovascular events and strokes, which is not commonly seen with other antihypertensive medications 64 , 79 81 .…”
Section: Discussionmentioning
confidence: 99%
“…For many years it has been well reported that RAS inhibition protects against renal interstitial fibrosis induced by UUO 69 , 71 73 . RAS activation has also been implicated in the development of cardiac fibrosis in CKD and ESRD patients 74 78 . Evidence from multiple randomized clinical trials supports the notion that inhibiting the RAS improves all causes of mortality and reduces adverse cardiovascular events and strokes, which is not commonly seen with other antihypertensive medications 64 , 79 81 .…”
Section: Discussionmentioning
confidence: 99%
“…In separate set of animals, renal function were measured as previously [10,16,17]. In 18 weeks after ACF induction, the animals (controls: n=9, HF: n=17) were placed in individual metabolic cages and their 24-hour urine was collected for determination of daily albuminuria.…”
Section: Renal Function Studies and Biochemistrymentioning
confidence: 99%
“…In 18 weeks after ACF induction, the animals (controls: n=9, HF: n=17) were placed in individual metabolic cages and their 24-hour urine was collected for determination of daily albuminuria. Urinary rat albumin was measured by the commercially available ELISA (ERA3201-1, AssayPro, MO, USA) [17]. In a randomly selected subgroup of animals surviving till 21 st week, control (n=6) and HF (n=8) animals were anesthetized and right jugular vein was catheterized for fluid and drug administration.…”
Section: Renal Function Studies and Biochemistrymentioning
confidence: 99%
“…The best example is the progression CKD in nondiabetic diseases: extreme diversity of initial pathological insult can substantially and unpredictably affect the clinical outcomes of any treatment regime. In contrast, an animal model that in experimental studies is commonly used to mimic the progression of CKD in nondiabetic diseases is strictly defined: 5/6 renal mass reduction (unilateral nephrectomy plus removal of two-thirds of the contralateral kidney, 5/6 NX), which leads to highly reproducible course of progression of CKD to end-stage renal disease, characterized by typical systemic and intrarenal activation of the RAAS, and predictable pathomorphological alterations in the remnant kidney (Carlstrom et al 2015, Červenka and Heller 1996, Kobori et al 2007, Kujal et al 2014, Neuringer and Brenner 1993, Remmuzi et al 2002, Sedláková et al 2017, Shimamura and Morrison 1975, Zoja et al 2006.…”
Section: Well-defined Condition or Disease In Animal Experiments Versmentioning
confidence: 99%
“…However, this combination failed to improve survival or event-free time in human trials; on the other hand, adverse effects were more frequent (Fried et al 2008, Mia et al 2011, Onuigbo 2009, Parving et al 2012, Yusuf and ONTARGET Investigators 2008b, Rutkowski and Tylicky 2015. Conversely, in most animal experiments not only that it has been undoubtedly proved that the inappropriate activation of the intrarenal RAAS is the major culprit of the progression of chronic kidney disease, but the treatment with the combination of ACEi and ARB proved successful and reliable, usually superior to application of a single drug in the slowing the progression of chronic kidney disease and development of end-organ damage (Azizi and Ménard 2004, Carlstrom et al 2015, Cao et al 2001, Cortinovis et al 2016, Červenka and Heller 1996, Doleželová et al 2016, Ke et al 2000, Kobori et al 2007, Kujal et al 2014, Macconi 2010, Richer et al 1998, Sen et al 2008, Shen et al 1998, Sedláková et al 2017, Zoja et al 2006, Zoja et al 2002. Experimental work obviously aims to bring about some progress in future treatment of patients so the discrepancy between the effects in the experiment and the clinics appeared to preclude the translation of experimental results to human medicine.…”
Section: Introductionmentioning
confidence: 99%